Capacity Costs, Heterogeneous Users, and Peak-Load Pricing - Jordan, W. John (Quarterly Journal of Economics, 1985)
Journal Article Capacity Costs, Heterogeneous Users, and Peak-Load Pricing Get access W. John Jordan W. John Jordan Seton Hall University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 100, Issue 4, November 1985, Pages 1335–1337, https://doi.org/10.2307/1885687 Published: 01 November 1985